Effects of Interfacial Reactions on Microstructures and Mechanical Properties of 3003 Al/T2 Cu and 1035 Al/T2 Cu Brazed Joints - Man Zhang (Crystals, 2020)
To meet the demand for efficient and reliable copper and aluminum (Cu/Al) joints in refrigeration and electric power industries, interfacial reactions in 3003 Al/T2 Cu and 1035 Al/T2 Cu joints brazed by Zn-xAl (x ranged from 2–25 wt.%) filler metals and their effects on the mechanical properties of the joints were investigated. Microstructures and fracture surfaces were observed combining with composition analysis. For 3003 Al/Cu joints, bulk CuAl and CuAl2 intermetallic compound (IMC) formed in brazing seams, and a CuAl IMC layer formed at the Cu side interfaces. For 1035 Al/Cu joints, bulk CuAl2 IMC formed in brazing seams, and an Al4.2Cu3.2Zn0.7 IMC layer formed at the Cu side interfaces. For both kinds of joints, shear strength increased first, then decreased with the increasing Al content. The increase in shear strength was because Al promoted the formation of Cu-Al IMC, and caused dispersion strengthening. With the excessive Al content, however, the bulk IMC became coarse and the IMC layers at Cu side interfaces grew thick, causing the joint strength to decrease due to stress concentration. The strength of 3003 Al/Cu joints was always higher than that of 1035 Al/Cu, and their highest strength were achieved by Zn-12Al and Zn-15Al, respectively.